Khaled Hosseini’s The Kite Runner: A Marxist Analysis - Tharu, Raj Kumar (Academia Research Journal, 2024)
This article attempts to analyze Khalid Hosseini’s novel The Kite Runner from a Marxist point of view. As a metaphor, Hosseini has used the word "runner" in the title of his novel to speak about one of the classes of people in our society. There are kite runners who run around screaming as they attempt to catch cut and falling kites during the kite flying contest. By looking at some major characters and their roles, an analysis has been presented from the perspective of Marxism. Additionally, the article tries to illustrate how there is an unexplained form of discrimination that prevails even in a friendship between the proletariat and the bourgeois. Despite that friendship appears to be working well namely to say between Amir and Hassan. This article is a qualitative research work for which the novel The Kite Runner has been used as the primary source of data. The secondary sources of data used in this research paper are articles published on it both physically and virtually. The discussion and analysis presented in this paper indicate that class struggles exist in various forms at various times, depending on the thoughts and actions of those individuals who are naturally inclined to maintain some sort of distinction that they appear to place a high value on, regardless of the nature of their relationship.